The Effect of Tai Chi Exercise on Reduction the Risk of Falls in the Elderly: A Literature Review - Novya Ashlahatul Mar'ah; Aprilina Sartika; Eka Sindi Miftahul Jannah; Neni Suryani; Dheni Wahyudi; Rodiah Pulungan; Rhury Nia Permata; Syamsul Anwar (STIKep PPNI Jawa Barat, 2022)
The risk of falls in the elderly increases with age. Even though there are many complications that occur if the elderly fall, Tai Chi exercise is one of the best fall prevention exercises, compared to other exercise programs that focus on muscle strength. Aims: This study aims to summarize studies on the effectiveness of Tai Chi Exercises to reduce falls in the elderly. Methods: a literature review using three databases (Pubmed, Google Scholar, and Sciendirect) for previous studies published from 2017 to 2022. The CASP format PRISMA guidelines and the PICOT framework were used to assess study quality assist in article selection, and define criteria—research inclusion. Results: A total of 5 articles from 65 studies were included in the review process. The results showed that Tai Chi exercise significantly reduced the risk and fear of falling in the elderly. The gentle and coordinated Tai Chi movements can increase the flexibility of the lower extremities. Conclusion: Tai Chi exercise can be ascertained as an activity for healthy elderly has many benefits, mainly to prevent the risk of falling.